Psychosocial Maturity, Autonomy, and Transition Readiness among Young Adults with Congenital Heart Disease or a Heart Transplant. (8th October 2015) - Mackie, Andrew S.; Rempel, Gwen R.; Islam, Sunjidatul; Rankin, Kathryn; McCurdy, Corinne; Vonder Muhll, Isabelle; Magill‐Evans, Joyce; Nicholas, David; Kovacs, Adrienne H.
Abstract: Objective: The population of young adults with congenital heart disease (CHD) or a heart transplant (HTx) is growing rapidly. These survivors require lifelong cardiology care and must assume self‐management responsibilities with respect to their health. Accordingly, we sought to assess psychosocial maturity and validity of the Transition Readiness Assessment Questionnaire (TRAQ) in this population. Design: The study was designed as a cross‐sectional observational study. Setting: The study was set at tertiary‐care pediatric and adult cardiology clinics in Edmonton and Toronto, Canada. Patients: The patients were 18‐ to 25‐year‐olds with moderate or complex CHD or a HTx in childhood. Outcome Measures: Participants completed validated instruments including the TRAQ, Erickson's Psychosocial Stage Inventory (EPSI), and Kenny's Parental Attachment Questionnaire (PAQ). Results: We enrolled 188 participants (41% women), 109 (58%) having moderate CHD, 64 (34%) complex CHD, and 15 (8%) with a HTx. Mean age for those followed in a pediatric clinic was 21.3 ± 2.3 years, compared with 21.8 ± 2.3 years for those attending an adult clinic ( P = 0.20). All questionnaire scores were similar among participants with moderate CHD vs. complex CHD vs. an HTx, and among participants followed in a pediatric clinic vs. an adult clinic. EPSI and PAQ scores were similar to those of healthy populations, though perception of maternal overprotection was common. TRAQ scores increased with age. A response of "not needed for my care" to 5 or more of the 29 TRAQ items was provided by 110 (75%) participants. Conclusions: Age, but not disease severity should be a factor when considering the transition needs of young adults with heart disease. The TRAQ has important limitations in the adult CHD/HTx population and a cardiac‐specific measure of transition readiness is needed.